2002
DOI: 10.1038/sj.bjp.0704677
|View full text |Cite
|
Sign up to set email alerts
|

Bretylium or 6‐OHDA‐resistant, action potential‐evoked Ca2+ transients in varicosities of the mouse vas deferens

Abstract: Action potential-evoked calcium transients in varicosities in mouse vas deferens were monitored using laser scanning confocal microscopy. Their signi®cance was examined by comparison with excitatory junction potentials (EJPs) and neurogenic contractions, both indirect measurements of transmitter release. Bretylium abolished EJPs, as well as the ATP and NA-mediated phases of contraction. However, bretylium revealed a prominent late component of contraction that was atropine-sensitive. Bretylium abolished calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Bretylium greatly reduced both the purinergic and noradrenergic components of electrically evoked responses. Continuous exposure (approximately 2–3 h) to bretylium revealed a residual hump-like contraction (at 200 stimuli), which increased in amplitude with time, reaching a maximum after about 5 h (see Jackson and Cunnane 2002) (Fig. 1, n =12, P <0.05).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Bretylium greatly reduced both the purinergic and noradrenergic components of electrically evoked responses. Continuous exposure (approximately 2–3 h) to bretylium revealed a residual hump-like contraction (at 200 stimuli), which increased in amplitude with time, reaching a maximum after about 5 h (see Jackson and Cunnane 2002) (Fig. 1, n =12, P <0.05).…”
Section: Resultsmentioning
confidence: 93%
“…In mouse vas deferens, contraction and confocal studies have shown that nicotine increases the amplitude of the bretylium-resistant contraction (Cuprian et al 2005) and spontaneous Ca 2+ transients in all varicosities, located on either bretylium-sensitive or bretylium-resistant nerve terminals (Brain et al 2001; Jackson et al 2001; Jackson and Cunnane 2002). These nerve terminals were considered to be preterminal sympathetic fibres, sensory nerves or cholinergic nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve fibres, originating from pelvic neurons in a discreet location in the pelvic ganglia supply the rat vas deferens (Keast 1992). A population of varicose nerves has been identified in the mouse vas deferens after destruction of sympathetic nerves by 6-hydroxydopamine (6-OHDA) (Jackson and Cunnane 2002). These nerves may be parasympathetic and/or sensory afferent fibres arising from L1, L2, L6 and S1 DRG travelling to the rat vas deferens in both hypogastric and pelvic nerves.…”
Section: Model Of Autonomic Neuroeffector Junctionmentioning
confidence: 99%
“…It has been argued that bretylium ( Boura and Green, 1959 ) prevents neurotransmitter release from sympathetic nerve terminals by abolishing the nerve terminal action potential ( Haeusler et al , 1969 ; Mitchell and Oates, 1970 ; Maxwell and Wastila, 1977 ; Brock and Cunnane, 1988 ); selectivity for sympathetic terminals occurs because bretylium is taken up into sympathetic terminals by a norepinephrine (NA) transporter‐1 (or uptake‐1). Hence, a potentially useful approach to identify noradrenergic terminals is to detect strings of varicosities in which the nerve action potential is abolished by bretylium ( Jackson and Cunnane, 2002 ). However, Jackson and Cunnane (2002) showed that bretylium (20 μ M ) does not abolish the action potential‐induced Ca 2+ transient in the majority of nerve terminal varicosities orthogradely loaded with the dextran conjugate of a Ca 2+ indicator.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a potentially useful approach to identify noradrenergic terminals is to detect strings of varicosities in which the nerve action potential is abolished by bretylium ( Jackson and Cunnane, 2002 ). However, Jackson and Cunnane (2002) showed that bretylium (20 μ M ) does not abolish the action potential‐induced Ca 2+ transient in the majority of nerve terminal varicosities orthogradely loaded with the dextran conjugate of a Ca 2+ indicator. This causes a dilemma because the innervation of the mouse vas deferens is predominantly sympathetic ( Taxi, 1965 ; Jones and Spriggs, 1975 ).…”
Section: Introductionmentioning
confidence: 99%